Full range optical and electrical properties of Zn-doped SnO2 and oxide/metal/oxide multilayer thin films deposited on flexible PET substrate - Cho, Yoonho; Parmar, Narendra S.; Nahm, Sahn; Choi, Ji-Won (ELSEVIER SCIENCE SA, 2017)
As a potential replacement of indium-tin oxide (ITO), Zn-doped SnO2/Ag/Zn-doped SnO2 multilayer transparent conducting electrodes were prepared on the flexible poly ethylene terephthalate (PET) substrates by RF sputtering at room temperature. To find the optimized composition of Zn-doped SnO2 thin film, which will have higher conductivity and transmittance as compared to the undoped SnO2 thin film, an off-axis Continuous Composition Spread (CCS) sputtering method was used. Zn-doped SnO2 thin films have lower resistivity than undoped SnO2 thin films due to excess oxygen vacancies (V-o) and/or zin interstitials (Zn-i) in thin films. The minimum resistivity of thin film was 0.13 Omega cm at optimized 2.43 wt% Zn-doping. Zn-doped SnO2/Ag/Zn-doped SnO2 multilayer thin films were prepared using the optimized composition deposited by an on-axis RF sputter. The multilayer TCO film has the resistivity similar to 5.33 x 10(-5) Omega cm and the average transmittance >85% in the 550 nm wavelength region. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: INDIUM-TIN-OXIDE; ROOM-TEMPERATURE; TRANSPARENT; GROWTH; ITO